ENHANCING STUDENTS’ TRANSLATION SKILLS DURING THE EARLY PHASE OF TRAINING (KONFERENSIYA, 2025)
This article outlines the basic principles of teaching translation in the professional sphere of communication. The focus is on developing basic written translation skills and abilities, enabling students to competently complete the main stages of text processing. Various methods of teaching professional translation techniques are analyzed. Particular attention is paid to working with dictionaries and reference manuals.